Class Management, How to Relate with Student's Interest in Learning? - Asmaa Azizatunnisa; Supardi Supardi; Juhji Juhji (Indonesian Journal of Islamic Educational Management, 2022)
This study aims to analyze class management, interest in learning, and the influence of class management on students' learning interests at SMP Maulana Hasanuddin Cilegon. The research method uses a survey. A total of 30 students were sampled in this study. The data collection technique used is the saturated sampling technique—data analysis using descriptive statistical analysis and inferential statistical analysis using simple regression. The results of the study can conclude that the level of class management of 67.26% is in the medium category, interest in learning of 66.36% is in the medium category, and there is a significant effect (0.857 > 0.374) between the variables of class management on interest in learning at a significant level 5%. Thus, this finding strengthens the previous results, and further research needs to be done regarding other variables that affect students' interest in learning.